2005
DOI: 10.1128/jcm.43.12.6007-6014.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Neisseria meningitidis Directly from Clinical Samples and Application of the Method to the Investigation of Meningococcal Disease Case Clusters

Abstract: Infections associated with Neisseria meningitidis are a major public health problem in England, Wales, and Northern Ireland. Currently, over 40% of cases are confirmed directly from clinical specimens using PCRbased methodologies without an organism being isolated. A nested/seminested multilocus sequence typing (MLST) system was developed at the Health Protection Agency Meningococcal Reference Unit to allow strain characterization beyond the serogroup for cases confirmed by PCR only. This system was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…PCR and Sanger sequencing were used for the remaining 28 DNAs obtained from culture-negative samples to determine ST, cc, porA and fetA (Birtles et al, 2005;Thompson et al, 2003). Briefly, for fetA gene amplification and sequencing, oligonucleotides described by Thompson et al (2003) were used.…”
Section: Methodsmentioning
confidence: 99%
“…PCR and Sanger sequencing were used for the remaining 28 DNAs obtained from culture-negative samples to determine ST, cc, porA and fetA (Birtles et al, 2005;Thompson et al, 2003). Briefly, for fetA gene amplification and sequencing, oligonucleotides described by Thompson et al (2003) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several techniques have been developed that allow these analyses on various body fluids (e.g., CSF, blood, urine, others) directly, further decreasing the utility of culture [40][41][42][43][44]. A recent study has demonstrated the utility of antigen detection kits, such as latex agglutination for serogroup determination during meningococcal epidemics [45].…”
Section: Serogroup Identificationmentioning
confidence: 99%
“…The amplification and sequencing of the porA and penA genes was carried out as described in Birtles et al (6) and Taha et al (22), respectively.…”
Section: Methodsmentioning
confidence: 99%